Reconfiguring Religious Authority in Islamic Education: Toward a Pedagogical Model of Critical Religious Literacy - Khumaini, Fahmi (Universitas Islam Indonesia, 2026)
This article examines the reconfiguration of religious authority in Islamic education by conseptualizing authority as a pedagogical formation rather than merely as a sociological or media-related phenomenon. The study responds to the tension between classical sources of authority grounded in ‘ilm, adab, sanad, teacher-student relations, and scholarly recognition, and contemporary sources mediated by formal institutions, academic credentials, bureaucratic certification, public communication, and algorithmic visibility. Employing library research with a historical-conceptual approach, this article analyzes selected scholarly works on Islamic intellectual tradition, educational institutions, pesantren, modern Islamic education, and digital Islam. The findings indicate that religious authority in Islamic education is formed through four interrelated dimensions: epistemic depth, ethical formation, institutional credibility, and digital literacy. The article concludes that Islamic education should cultivate critical religious literacy by enabling students so they can distinguish scholarly legitimacy from popularity, credentials from competence, and digital visibility from epistemic accountability.